Bank Capital and Lending : An Extended Framework and Evidence of Nonlinearity - Catalan, Mario; Anggadewi Harun, Cicilia; Hoffmaister, Alexander (Washington, D.C. : International Monetary Fund, 2017)
This paper studies the transmission of bank capital shocks to loan supply in Indonesia. A series of theoretically founded dynamic panel data models are estimated and find nonlinear effects of capital on loan growth: the response of weaker banks to changes in their capital positions is larger than that of stronger banks. This non-linearity implies that not only the level of capital but also its distribution across banks in the financial system affects the transmission of shocks to aggregate lending. Likewise, the effects of bank recapitalization on loan growth depend on banks' starting capital positions and the size of capital injections.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet